Automobile interior fabric and preparation method and application thereof

By performing ammonia plasma treatment and zinc nitrate complexing on aluminum silicate fibers, and generating ammonia magnesium phosphate in polyimide resin and doping nanotitanium dioxide, the problem of poor flame retardant and antibacterial performance of existing automotive interior materials is solved, and efficient flame retardant and antibacterial effects are achieved.

CN115874332BActive Publication Date: 2025-04-01DONGHUA UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211314742.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2025-04-01
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The flame retardant and antibacterial properties of existing automotive interior materials limit their application in automotive interiors.

Method used

By subjecting the ammonia plasma treatment of the aluminum silicate fibers to the aluminum silicate fibers, the active carboxyl and halogen elements are introduced, and they are immersed in zinc nitrate solution for complexing, thereby enhancing the flame retardant and antibacterial properties. At the same time, magnesium nitrate and ammonia phosphate are used to generate magnesium ammonia phosphate in the polyimide resin and dopant nanotitanium dioxide to improve the flame retardant effect.

Benefits of technology

The prepared car interior fabrics still maintain good antibacterial properties and flame retardant effects after multiple washes, which significantly improves the safety and environmental protection of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003908681690000071
    Figure BDA0003908681690000071
  • Figure BDA0003908681690000081
    Figure BDA0003908681690000081
  • Figure BDA0003908681690000082
    Figure BDA0003908681690000082
Patent Text Reader

Abstract

The invention discloses an automobile interior fabric and a preparation method and application thereof. The invention first processes aluminum silicate fiber, introduces amino groups on the surface of the aluminum silicate fiber, and then uses the amino groups to react with tetrabromophthalic anhydride, thereby introducing active carboxyl groups, halogen elements and long-chain alkyl groups on the surface of the aluminum silicate fiber, thereby enhancing the flame retardant performance of the aluminum silicate fiber; at the same time, the modified aluminum silicate fiber is immersed in a zinc nitrate solution, and zinc ions are fixed on the surface of the aluminum silicate fiber through the chelation of carboxyl groups, thereby enhancing the antibacterial performance of the aluminum silicate fiber; at the same time, magnesium nitrate and ammonium phosphate can react to generate ammonium magnesium phosphate on the surface of a polyimide resin, and nano titanium dioxide is doped in the ammonium magnesium phosphate, and the ammonium magnesium phosphate reacts to generate non-flammable gas during the decomposition process, thereby reducing the concentration of combustibles, and the nano titanium dioxide has the function of absorbing smoke, which can reduce the generation of toxic smoke and further improve the flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric preparation, and in particular to an automobile interior fabric and a preparation method and application thereof. Background Art

[0002] In recent years, with the changes in consumer demand and concepts, automotive interior materials must not only meet the requirements of practicality, economy, and durability, but also develop in the direction of humanization, comfort, aesthetics, and environmental protection.

[0003] At present, the most widely used material in automobiles is polyurethane. The full name of polyurethane is polyurethane. It is a new type of organic polymer material that can meet the comfort, safety, lightweight and green environmental protection requirements of modern automobile interiors. However, polyurethane itself is extremely flammable, with a limiting oxygen index (LOI) below 18%. It is easily ignited in the air and produces a large amount of toxic smoke after combustion, which greatly limits its scope of use in automobile interior materials.

[0004] Therefore, it is particularly important to develop a material with good mechanical properties, flame retardant properties and antibacterial properties for use in automotive interiors. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an automotive interior fabric and a preparation method and application thereof, so as to solve the technical problem that the existing automotive interior materials have poor flame retardant and antibacterial properties.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for preparing an automobile interior fabric comprises the following steps:

[0008] (1) placing aluminum silicate fibers in a plasma treatment chamber, evacuating the chamber, and treating the chamber with ammonia plasma to obtain pretreated aluminum silicate fibers;

[0009] (2) ultrasonically dispersing the pretreated aluminum silicate fiber in N,N-dimethylformamide solvent, then adding tetrabromophthalic anhydride, stirring and reacting at room temperature for 2-4 hours, and after the reaction is completed, washing and drying the obtained product to obtain modified aluminum silicate fiber;

[0010] (3) immersing the modified aluminum silicate fiber in a zinc nitrate solution, uniformly dispersing it by ultrasonication, and then adsorbing it by oscillation for 3-5 hours. After the adsorption is completed, filtering, washing, and drying are performed to obtain a modified aluminum silicate fiber complex;

[0011] (4) ultrasonically dispersing the polyimide resin and nano-titanium dioxide in deionized water, then adding magnesium nitrate and ammonium phosphate, adjusting the pH of the solution to 9-11, stirring and reacting for 2-3 hours, and after the reaction is completed, filtering, washing, and drying the reaction product to obtain a modified polyimide resin;

[0012] (5) adding the modified polyimide resin into a screw injection molding machine, heating and melting the resin for spinning, and stretching the resin under the action of hot air to obtain modified polyimide resin fibers;

[0013] (6) The modified aluminum silicate fiber complex and the modified polyimide resin fiber are spun into filaments through a spinning machine to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, respectively. The aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric.

[0014] Preferably, in step (1), the treatment power of the ammonia plasma is 300-500 W, and the treatment time is 3-5 min.

[0015] Preferably, in step (2), the mass ratio of pretreated aluminum silicate fiber to tetrabromophthalic anhydride is 10-15:5-8.

[0016] Preferably, in step (3), the mass ratio of the modified aluminum silicate fiber to the zinc nitrate solution is 8-12:100.

[0017] Preferably, in step (3), the mass fraction of the zinc nitrate solution is 1-2%.

[0018] Preferably, in step (4), the mass ratio of polyimide resin, nano-titanium dioxide, magnesium nitrate and ammonium phosphate is 40-60:3-5:6-10:10-15.

[0019] Preferably, in step (6), the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 4-5:4-6.

[0020] Preferably, in step (6), the warp yarn density is 60-80, and the weft yarn density is 60-80.

[0021] The present invention provides automobile interior trim fabrics prepared by the preparation method.

[0022] The invention also provides application of the automobile interior fabric in automobile seat covers or roof interiors.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention first treats aluminum silicate fiber with ammonia plasma to introduce amino groups on the surface of the aluminum silicate fiber, and then uses the amino groups to react with tetrabromophthalic anhydride, thereby introducing active carboxyl groups, halogen elements and long-chain alkyl groups on the surface of the aluminum silicate fiber, thereby enhancing the flame retardant properties of the aluminum silicate fiber; at the same time, the modified aluminum silicate fiber is immersed in a zinc nitrate solution, and the zinc ions are fixed on the surface of the aluminum silicate fiber through the chelation of the carboxyl groups, thereby enhancing the antibacterial properties of the aluminum silicate fiber.

[0025] (2) Magnesium nitrate and ammonium phosphate can react to generate magnesium ammonium phosphate on the surface of the polyimide resin. At the same time, nano-titanium dioxide is doped in the magnesium ammonium phosphate. The magnesium ammonium phosphate reacts to generate non-flammable gas during the decomposition process, thereby reducing the concentration of combustibles. The nano-titanium dioxide doped in the magnesium ammonium phosphate has the function of absorbing smoke, which can reduce the generation of toxic smoke, thereby further improving the flame retardant effect.

[0026] (3) The automotive interior fabric prepared by the present invention still has good antibacterial properties and flame retardant effects after multiple washings. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0028] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0029] The aluminum silicate fiber used in the embodiment of the present invention was purchased from Hebei Zexu Building Materials Technology Development Co., Ltd.

[0030] Polyimide resin was purchased from Hubei Biaoyue Biotechnology Development Co., Ltd.;

[0031] Nano-titanium dioxide was purchased from Shandong Juxin Chemical Trading Co., Ltd.

[0032] Example 1

[0033] A method for preparing an automobile interior fabric comprises the following steps:

[0034] (1) placing 20 g of aluminum silicate fiber in a plasma treatment chamber, evacuating the chamber, and treating the fiber with ammonia plasma at a treatment power of 300 W for a treatment time of 3 min to obtain pretreated aluminum silicate fiber;

[0035] (2) 10 g of pretreated aluminum silicate fiber was ultrasonically dispersed in 200 mL of N,N-dimethylformamide solvent, and then 5 g of tetrabromophthalic anhydride was added, and the mixture was stirred at room temperature for 2 h. After the reaction was completed, the obtained product was washed and dried to obtain modified aluminum silicate fiber;

[0036] (3) 10 g of modified aluminum silicate fiber was immersed in 100 g of 1 wt% zinc nitrate solution, ultrasonically dispersed evenly, and then oscillated and adsorbed for 3 h. After the adsorption was completed, the modified aluminum silicate fiber was filtered, washed, and dried to obtain a modified aluminum silicate fiber complex;

[0037] (4) 40 g of polyimide resin and 3 g of nano-titanium dioxide were ultrasonically dispersed in 400 g of deionized water, and then 6 g of magnesium nitrate and 10 g of ammonium phosphate were added, and the pH of the solution was adjusted to 9 with ammonia water, and the reaction was stirred for 2 h. After the reaction was completed, the reaction product was filtered, washed, and dried to obtain a modified polyimide resin;

[0038] (5) adding 40 g of modified polyimide resin into a screw injection molding machine, heating and melting the mixture for spinning, and stretching the mixture under the action of hot air to obtain modified polyimide resin fibers;

[0039] (6) The modified aluminum silicate fiber complex and the modified polyimide resin fiber are spun into filaments by a spinning machine to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, respectively. The aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric, wherein the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 5:5, the warp yarn density is 60s, and the weft yarn density is 60s.

[0040] Example 2

[0041] A method for preparing an automobile interior fabric comprises the following steps:

[0042] (1) placing 20 g of aluminum silicate fiber in a plasma treatment chamber, evacuating the chamber, and treating the fiber with ammonia plasma at a treatment power of 500 W for a treatment time of 4 min to obtain pretreated aluminum silicate fiber;

[0043] (2) 15 g of pretreated aluminum silicate fiber was ultrasonically dispersed in 200 mL of N,N-dimethylformamide solvent, and then 8 g of tetrabromophthalic anhydride was added, and the mixture was stirred at room temperature for 3 h. After the reaction was completed, the obtained product was washed and dried to obtain modified aluminum silicate fiber;

[0044] (3) 8 g of modified aluminum silicate fiber was immersed in 100 g of 2 wt% zinc nitrate solution, ultrasonically dispersed evenly, and then oscillated and adsorbed for 5 h. After the adsorption was completed, the fiber was filtered, washed, and dried to obtain a modified aluminum silicate fiber complex;

[0045] (4) 60 g of polyimide resin and 5 g of nano-titanium dioxide were ultrasonically dispersed in 400 g of deionized water, and then 10 g of magnesium nitrate and 15 g of ammonium phosphate were added, and the pH of the solution was adjusted to 11 with ammonia water, and the reaction was stirred for 3 h. After the reaction was completed, the reaction product was filtered, washed, and dried to obtain a modified polyimide resin;

[0046] (5) adding 40 g of modified polyimide resin into a screw injection molding machine, heating and melting the mixture for spinning, and stretching the mixture under the action of hot air to obtain modified polyimide resin fibers;

[0047] (6) The modified aluminum silicate fiber complex and the modified polyimide resin fiber are spun into filaments by a spinning machine respectively to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, and the aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric, wherein the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 4:6, the warp yarn density is 80s, and the weft yarn density is 80s.

[0048] Example 3

[0049] A method for preparing an automobile interior fabric comprises the following steps:

[0050] (1) placing 20 g of aluminum silicate fiber in a plasma treatment chamber, evacuating the chamber, and treating the fiber with ammonia plasma at a treatment power of 400 W for a treatment time of 5 min to obtain pretreated aluminum silicate fiber;

[0051] (2) 12 g of pretreated aluminum silicate fiber was ultrasonically dispersed in 200 mL of N,N-dimethylformamide solvent, and then 6 g of tetrabromophthalic anhydride was added, and the mixture was stirred at room temperature for 4 h. After the reaction was completed, the obtained product was washed and dried to obtain modified aluminum silicate fiber;

[0052] (3) 12 g of modified aluminum silicate fiber was immersed in 100 g of 1.5 wt% zinc nitrate solution, ultrasonically dispersed evenly, and then oscillated and adsorbed for 4 h. After the adsorption was completed, the fiber was filtered, washed, and dried to obtain a modified aluminum silicate fiber complex;

[0053] (4) 50 g of polyimide resin and 4 g of nano-titanium dioxide were ultrasonically dispersed in 400 g of deionized water, and then 8 g of magnesium nitrate and 12 g of ammonium phosphate were added, and the pH of the solution was adjusted to 10 with ammonia water, and the reaction was stirred for 3 h. After the reaction was completed, the reaction product was filtered, washed, and dried to obtain a modified polyimide resin;

[0054] (5) adding 40 g of modified polyimide resin into a screw injection molding machine, heating and melting the mixture for spinning, and stretching the mixture under the action of hot air to obtain modified polyimide resin fibers;

[0055] (6) The modified aluminum silicate fiber complex and the modified polyimide resin fiber are spun into filaments by a spinning machine to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, respectively. The aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric, wherein the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 5:5, the warp yarn density is 80s, and the weft yarn density is 80s.

[0056] Comparative Example 1

[0057] A method for preparing an automobile interior fabric comprises the following steps:

[0058] (1) placing 20 g of aluminum silicate fiber in a plasma treatment chamber, evacuating the chamber, and treating the fiber with ammonia plasma at a treatment power of 400 W for a treatment time of 5 min to obtain pretreated aluminum silicate fiber;

[0059] (2) 12 g of pretreated aluminum silicate fiber was ultrasonically dispersed in 200 mL of N,N-dimethylformamide solvent, and then 6 g of tetrabromophthalic anhydride was added, and the mixture was stirred at room temperature for 4 h. After the reaction was completed, the obtained product was washed and dried to obtain modified aluminum silicate fiber;

[0060] (3) adding 40 g of polyimide resin into a screw injection molding machine, heating and melting the fibers, and stretching the fibers under the action of hot air to obtain polyimide resin fibers;

[0061] (4) The modified aluminum silicate fiber complex and the polyimide resin fiber are spun into filaments by a spinning machine to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, respectively. The aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric, wherein the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 5:5, the warp yarn density is 80s, and the weft yarn density is 80s.

[0062] Comparative Example 2

[0063] A method for preparing an automobile interior fabric comprises the following steps:

[0064] (1) 50 g of polyimide resin and 4 g of nano-titanium dioxide were ultrasonically dispersed in 400 g of deionized water, and then 8 g of magnesium nitrate and 12 g of ammonium phosphate were added, and the pH of the solution was adjusted to 10 with ammonia water, and the reaction was stirred for 3 hours. After the reaction was completed, the reaction product was filtered, washed, and dried to obtain a modified polyimide resin;

[0065] (2) adding 40 g of modified polyimide resin into a screw injection molding machine, heating and melting the resin, and stretching the resin under hot air to obtain modified polyimide resin fibers;

[0066] (3) Aluminum silicate fiber and modified polyimide resin fiber are spun into filaments through a spinning machine respectively to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, and the aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric, wherein the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 5:5, the warp yarn density is 80s, and the weft yarn density is 80s.

[0067] The flame retardant properties of the fabrics prepared in Examples 1-3 and Comparative Examples 1-2 were tested in accordance with GB / T5454-1997. The fabric samples were then washed 30 times using a washing method of a color fastness tester as a reference. The flame retardant properties of the fabric samples were retested. The test results are shown in Table 1:

[0068] Table 1

[0069]

[0070]

[0071] The antibacterial performance of the fabrics prepared in Examples 1-3 and Comparative Example 2 was tested according to the detection method of GB / T20944.3-2008 "Evaluation of Antibacterial Performance of Textiles Part 3: Oscillation Method", the detection bacteria was Escherichia coli, and then the washing method of the washing color fastness tester was used as a reference, the fabric samples were washed 30 times, and the antibacterial performance of the fabric samples was retested. The results are shown in Table 2:

[0072] Table 2

[0073]

[0074] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing an automobile interior fabric, characterized in that: The steps include: (1) placing aluminum silicate fibers in a plasma treatment chamber, evacuating the chamber, and treating the chamber with ammonia plasma to obtain pretreated aluminum silicate fibers; (2) ultrasonically dispersing the pretreated aluminum silicate fiber in N,N-dimethylformamide solvent, then adding tetrabromophthalic anhydride, stirring and reacting at room temperature for 2-4 hours, and after the reaction is completed, washing and drying the obtained product to obtain modified aluminum silicate fiber; (3) immersing the modified aluminum silicate fiber in a zinc nitrate solution, uniformly dispersing it by ultrasonication, and then oscillating and adsorbing it for 3-5 hours. After the adsorption is completed, filtering, washing, and drying are performed to obtain a modified aluminum silicate fiber complex; (4) ultrasonically dispersing the polyimide resin and nano-titanium dioxide in deionized water, then adding magnesium nitrate and ammonium phosphate, adjusting the pH of the solution to 9-11, stirring and reacting for 2-3 hours, and after the reaction is completed, filtering, washing, and drying the reaction product to obtain a modified polyimide resin; (5) adding the modified polyimide resin into a screw injection molding machine, heating and melting the resin for spinning, and stretching the resin under the action of hot air to obtain modified polyimide resin fibers; (6) The modified aluminum silicate fiber complex and the modified polyimide resin fiber are spun into filaments through a spinning machine to obtain aluminum silicate fiber yarn and polyimide resin fiber yarn, respectively. The aluminum silicate fiber yarn is used as the warp and the polyimide resin fiber yarn is used as the weft to weave the automotive interior fabric.

2. The preparation method according to claim 1, characterized in that: In step (1), the processing power of the ammonia plasma is 300-500W, and the processing time is 3-5min.

3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the pretreated aluminum silicate fiber to tetrabromophthalic anhydride is 10-15:5-8.

4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the modified aluminum silicate fiber to the zinc nitrate solution is 8-12:

100.

5. The preparation method according to claim 1, characterized in that: In step (3), the mass fraction of the zinc nitrate solution is 1-2%.

6. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of polyimide resin, nano-titanium dioxide, magnesium nitrate and ammonium phosphate is 40-60:3-5:6-10:10-15.

7. The preparation method according to claim 1, characterized in that: In step (6), the mass ratio of the aluminum silicate fiber yarn to the polyimide resin fiber yarn is 4-5:4-6.

8. The preparation method according to claim 1, characterized in that: In step (6), the warp yarn density is 60-80, and the weft yarn density is 60-80.

9. The automotive interior fabric prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the automobile interior fabric as claimed in claim 9 in automobile seat covers or roof interiors.

Citation Information

Patent Citations

  • Heat-resistant fiber paint

    CN104893563A

  • Glass fiber chenille yarn

    CN105200602A